ΑΝΑΕΡΟΒΙΑ ΧΩΝΕΥΣΗ ΥΓΡΩΝ ΑΠΟΒΛΗΤΩΝ ΒΙΟΜΗΧΑΝΙΩΝ ΚΑΛΛΥΝΤΙΚΩΝ ΜΕΤΑ ΑΠΟ ΟΞΕΙΔΩΤΙΚΕΣ ΔΙΕΡΓΑΣΙΕΣ ΜΕ ΑΝΤΙΔΡΑΣΤΗΡΙΑ FENTON - ΚΑΝΕΛΛΟΠΟΥΛΟΣ, ΔΗΜΗΤΡΙΟΣ (Σχολή Χημικών Μηχανικών, 2016)
Cosmetic industry is a fast growing industry with 7.2 billion Euros income from retail sales in Europe for 2004 and over 1.7 million employers. Cosmetic industry wastewater in characterized from high concentrations of COD, Total Suspended Solids(TSS), detergents, oil and fat and high ratio for COD/BOD which makes them difficult to undergo direct biological treatment. For this reason a number of pre treatment technologies have been examined. The current thesis examines the cosmetic wastewater from a typical cometic industry and focuses on the efficiency of Fenton reagent in the removal of total organic carbon (TOC) which is an important parameter showing the strength of the wastewater. In addition to that examines changes in the biodegradability of the wastewater from Fenton reagents. In this study, after the chemical treatment of the wastewater, anaerobic digestion is being examined as an effective way of treatment with the help of a 5 l laboratory scale anaerobic digester which through a PLC can record methane and biogas production. In addition to the above, there is a process description of the typical wastewater treatment plant using as a pretreatment coagulation with PAC and the pros and cons which has the use of Fenton reagent. The Main findings from the phD thesis are described below: • from the examination of a series of grab samples taken from the wastewater treatment plant it was found that although the plant uses over 500 deferent chemical substances the mail wastewater parameters such as COD,TOC, TSS , fats and oil are kept within a close range. • the use of Fenton reagent in the wastewater has a positive effect to the TOC reduction and the optimum concentrations of hydrogen peroxide and iron sulfate was found. • We the help of IBM SPSS statistics a non linear equation was developed which correlates the hydrogen peroxide and iron sulfate concentration in the solution in relation to the TOC removal. • it was examined the use of anaerobic treatment after treatment with Fenton reagent and defined the optimum degree of chemical pre treatment for increased methane generation.